Implications of a Genetic Etiology for Renal Transplant: Early-Onset Alport Syndrome with a Novel Mutation - Singh, Ravi Kumar; Arora, Veronica; Tiwari, Vaibhav; Gupta, Deepti; Gupta, Anurag; Puri, Ratna Dua (Journal of Pediatric Genetics, 2020)
Alport's syndrome (AS) is a rare disorder characterized by a triad of deafness, progressive renal dysfunction, and ocular abnormalities. We presented a patient of early onset AS with a novel frameshift pathogenic variant in the COL4A5 gene and discuss the utility of genetic testing in the family as well as for the transplant recipient. The patient was a 17-year-old adolescent male with end-stage renal disease (ESRD) and hearing loss. In the setting of ESRD, since hearing loss and anterior lenticonus was detected on an ophthalmologic exam, AS was suspected. On genetic testing, a novel hemizygous frameshift variant was identified in the COL4A5 gene (c.1392del (p.Asp464GlufsTer10)), which was also segregated in the family. In this report, we discussed the early severe presentation, typical ocular findings, genotype–phenotype correlation, and implications of genetic testing for renal transplant. We also explored the challenges of genetic testing in developing countries and the potential of pharmacogenomics.
Keywords: COL4A5; deafness; genetic; ocular; kidney transplantation